Paternalistic Leadership and Employee Responses in Javanese Culture - Irawanto, Dodi W.; Ramsey, Phil L. (Gadjah Mada International Journal of Business, 2011)
While much has been written about leadership research, little effort has been made to identify what constitutes effective leadership in an Indonesian cultural context. Paternalistic leadership is an emerging body of research that has been adapted to the Indonesian context. Javanese cultural values provide a foundation for an Indonesian form of Paternalistic Leadership (PLI). In this study, 178 civil servants in the province of Yogyakarta Special Region, where surveyed in order to examine their responses to the dimensions of PLI. Results suggested that effective PLI emphasises a leaderâs visibility, benevolence and courage. Authority and impartiality need to be expressed in ways that align with traditional Javanese values. Suggestions of the direction for further study are presented.Â Â Â Â Â